2020
DOI: 10.1080/17522439.2020.1742199
|View full text |Cite
|
Sign up to set email alerts
|

Inflexibility processes as predictors of social functioning in chronic psychosis

Abstract: Within the context of a transdiagnostic perspective, the Psychological Inflexibility (PI) construct refers to rigid attempts to control undesirable private events at the expense of value-guided actions. Given the framework of PI as a construct associated with poor recovery and social functioning in people with psychosis, the main objective was to explore the role of two processes related to inflexibility (experiential avoidance, -EA-, and self-concealment) in predicting social functioning. The study sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…This is in line with previous research suggesting CF as a core process of PF constitutes a mechanism of change in third-wave CBT in individuals with schizophrenia ( 20 , 43 ). However, while research has shown components of PF to be predictors of social functioning ( 35 ), as well as individual difference factors for psychosis ( 37 , 67 ), in the present study CF was not found to significantly mediate the relationship between mindfulness and overall symptom severity as measured by the PANSS. Therefore, this study highlights the central role of mindfulness and CF as a compoment of PF in treating negative symptoms in particular.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous research suggesting CF as a core process of PF constitutes a mechanism of change in third-wave CBT in individuals with schizophrenia ( 20 , 43 ). However, while research has shown components of PF to be predictors of social functioning ( 35 ), as well as individual difference factors for psychosis ( 37 , 67 ), in the present study CF was not found to significantly mediate the relationship between mindfulness and overall symptom severity as measured by the PANSS. Therefore, this study highlights the central role of mindfulness and CF as a compoment of PF in treating negative symptoms in particular.…”
Section: Discussioncontrasting
confidence: 90%
“…The other two dimensions, committed action and values, go beyond that concept and are rather behavioral change processes related to CBT guiding persons to become more engaged and active in their lives ( 34 ). PF is hypothesized to be negatively impacted by two core processes: cognitive fusion, namely getting caught in thoughts or emotions, and experiential avoidance, referring to the avoidance or repression of thoughts and emotions ( 35 37 ). PF displays a complex construct describing the mechanism of change in the ACT process.…”
Section: Introductionmentioning
confidence: 99%
“…Concealment of one's illness is another of the coping behaviours most commonly reported by participants. The previous literature has documented that both active avoidance and self-concealment represent paradoxical coping strategies that are commonly employed by people with psychosis [36][37][38]. Overall, everything seems to confirm that people with psychosis maintain a defensive and intolerant relationship towards their own disorder.…”
Section: Discussionmentioning
confidence: 73%
“…Psychological flexibility includes changing behavior that compromises personal or social functioning. As previous studies have shown [ 31 ], the inflexibility observed in patients with poor social functioning suggests a struggle with symptoms, which impedes patients from becoming the managers of their own lives and, in the long run, invades and disrupts all the facets that generally define their lives (e.g., work, intimate relations, family relations, etc.). Maintaining a balance between important life domains and being aware, open, and committed to behaviors that are congruent with deeply rooted values would not only help to improve social functioning, but also provide an integral approach to psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic psychosis, PI has been demonstrated to be a predictor of self-stigma [ 29 , 30 ] and negative results in various social-functioning domains [ 31 ]. Interventions targeting acceptance and psychological flexibility (such as ACT) have been shown to increase resistance to stigma [ 32 ], promoting personal recovery [ 33 ] and reducing the pernicious effects of self-stigma in those diagnosed with schizophrenia [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%